Tradisi Petik Laut dalam Komodifikasi Pariwisata Sendang Biru - Rahayuningtyas, Dyah; Siahaya, Thiovilia (Studi Budaya Nusantara, 2017)
Abstract Indonesia is a country that has a diversity both geographically and culturally. Through the diversity of Indonesia can develop resources in that is quite abundant as a tourist destination. One of the potential to be developed is the coastal area with all the cultures and communities, for example is